High-temperature X-ray absorption spectroscopy study of thermochromic copper molybdate. (15th October 2019) - Jonane, Inga; Anspoks, Andris; Aquilanti, Giuliana; Kuzmin, Alexei
Abstract: X-ray absorption spectroscopy at the Cu and Mo K-edges was used to study the effect of heating on the local atomic structure and dynamics in copper molybdate ( α -CuMoO4 ) in the temperature range from 296 to 973 K. The reverse Monte-Carlo (RMC) method was successfully employed to perform accurate simulations of EXAFS spectra at both absorption edges simultaneously. The method allowed us to determine structural models of α -CuMoO4 being consistent with the experimental EXAFS data. These models were further used to follow temperature dependencies of the local environment of copper and molybdenum atoms and to obtain the mean-square relative displacements for Cu–O and Mo–O atom pairs. Moreover, the same models were able to interpret strong temperature-dependence of the Cu K-edge XANES spectra. We found that the local environment of copper atoms is more affected by thermal disorder than that of molybdenum atoms. While the MoO4 tetrahedra behave mostly as the rigid units, a reduction of correlation in atomic motion between copper and axial oxygen atoms occurs upon heating. This dynamic effect seems to be the main responsible for the temperature-induced changes in the O 2− →Cu 2+ charge transfer processes and, thus, is the origin of the thermochromic properties of α -CuMoO4 upon heating above room temperature. Graphical abstract: Image 1